A New Approach for Representing Photonic Crystal Fiber Index Profile to Determine their Optical Characteristics - Shaker, Maan M.; Majeed, Mahmood Sh.; Daoud, Raid W. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
A genetic algorithm is implemented to represent the different shapes of Photonic Crystal Fiber (PCF) profile; this is due to the fact that such fibers have special structure. A novel approach is suggested which differs from the usual fibers. By applying this new approach, more realistic representations of their profiles are drawn and hence highly accurate results are obtained including propagation and dispersion characteristics.